THE HISTORY AND ROLE OF SCHOLARS IN THE DEVELOPMENT OF HADITH IN THE BASRAH REGION IN THE FIRST AND SECOND CENTURIES - muftih, muftihun najah (Yayasan Baitul Hikmah al-Zain, 2024)
This study discusses the development of hadith in the Basrah region, which includes the history of the development of the city of Basrah. Basrah which used to serve as a military base during the expansion period of the Persian conquests under the leadership of Umar ibn Khatab, to its transformation into an intellectually and strategically advanced urban center. This transformation was driven by Basrah's strategic geographical location and became home to a number of important companions such as Utbah ibn Ghazawan, Anas ibn Malik, Abdullah ibn Abbas, and others. This research uses a descriptive analytical approach by relying on the study of relevant primary literature. The main objective of the study was to uncover the role and development of hadith scholars in the first and second centuries of Hijrah in the Basrah region. The findings of the study highlight the significant contributions of various companions and tabi'in figures in enriching and developing the tradition of hadith in Basrah. Their main focus was not only limited to the collection of traditions but also on the development of sanad criticism which was the forerunner of an important methodology for evaluating and verifying the authenticity of traditions that influenced the development of hadith scholarship at large.